The relationship of locus control, coping strategies, and perceived stereotypes of male homosexual teens in Iloilo. - Dela Cruz, Karren Jean M.
There have been a lot of western studies conducted about homosexuals. This descriptive study focuses on male homosexuals teens aged 12-19 in Iloilo. Specifically, it ventures on the relationship of locus of control, coping strategies and their perceived prejudies. There were a total of 30 respondents and 8 of which participated in the FGD., The results show that most of the respondents have internal locus of control, employs problem-focused coping, and have negative perceived stereotypes. It also shows that among homosexual teens there is no relationship between their type coping strategy and type of locus of control.